Using intervention mapping to develop 'ROSE': an intervention to support peer workers in overdose response settings - Zahra Mamdani; Sophie McKenzie; Fred Cameron; Mike Knott; Jennifer Conway-Brown; Tracy Scott; Jane A. Buxton; Bernie Pauly (BMC, 2021)
Abstract Background Peer workers (those with lived/living experience of substance use working in overdose response settings) are at the forefront of overdose response initiatives in British Columbia (BC). Working in these settings can be stressful, with lasting social, mental and emotional impacts. Peer workers have also been disproportionately burdened by the current dual public health crises characterized by the onset of the COVID-19 pandemic and rise in illicit drug overdose deaths. It is therefore critical to develop supports tailored specifically to their realities. Methods We used the six steps outlined in the Intervention Mapping (IM) framework to identify needs of peer workers and design an intervention model to support peer workers in overdose response settings. Results Eight peer-led focus groups were conducted in community settings to identify peer workers' needs and transcripts were analyzed using interpretive description. The strategies within the intervention model were informed by organizational development theory as well as by lived/living experience of peer workers. The support needs identified by peer workers were categorized into three key themes and these formed the basis of an intervention model titled 'ROSE'; R stands for Recognition of peer work, O for Organizational support, S for Skill development and E for Everyone. The ROSE model aims to facilitate cultural changes within organizations, leading towards more equitable and just workplaces for peer workers. This, in turn, has the potential for positive socio-ecological impact. Conclusions Centering lived/living experience in the intervention mapping process led us to develop a framework for supporting peer workers in BC. The ROSE model can be used as a baseline for other organizations employing peer workers.